Foreign direct investment motives and location decision factors under economic recession: Three cases of Finnish FDI in Portugal - Mankinen, Maria (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The purpose of this thesis was to study how uncertainty in economic conditions of the FDI host country affects location decision of an investment, and what kinds of motives are behind the investment decision to a country in economic recession, in this case Portugal. The country has attracted foreign direct investment steadily, but it is evident that most multinational firms and investors tend to be more interested in emerging economies in general. The aim was to find out also which host country specific advantages are important in this kind of cross-border investment and which factors are important for an FDI to succeed under economic uncertainty at the host country. The study was done by analyzing three Finnish case companies: a private equity and real estate investment firm Pontos Group, A wave energy technology research and development company AW Energy and NSN, Nokia Solutions and Networks, a global telecommunications company. The research was done empirically, by interviewing experts on the subject, mainly persons representing these companies. In addition relevant articles, journals and content from case companies’ web-pages is used for the desk research regarding the topic. The results of this thesis showed that the FDIs with strategic asset-seeking investments seem most profitable FDI types under uncertain economic conditions. This kind of investments aim to strengthen the company’s long-term strategy, including the time after recession. Firm-specific ownership advantages that bring competitive advantage proved out to be important under these circumstances, as well as first-mover advantages and externally created assets such as government promotional policies regarding FDI incentives. Also the location was considered suitable for resource- or efficiency seeking motives, based on the lowered price level at the host country. Problems were related mainly to financing, but as foreign companies receive financing usually from their home countries, the economic recession of the host country does not have significant effect for FDI decision, according to this study